2010
DOI: 10.1152/physiolgenomics.00100.2010
|View full text |Cite
|
Sign up to set email alerts
|

Fine-mapping of muscle weight QTL in LG/J and SM/J intercrosses

Abstract: Lionikas A, Cheng R, Lim JE, Palmer AA, Blizard DA. Finemapping of muscle weight QTL in LG/J and SM/J intercrosses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

9
74
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(83 citation statements)
references
References 44 publications
9
74
0
Order By: Relevance
“…AILs have been employed in several previous studies to successfully map QTL for complex traits in mice, including locomotor activity , muscle weight (Lionikas et al 2010), red blood cell characteristics (Bartnikas et al 2012), body weight , methamphetamine sensitivity (Parker et al 2012a), prepulse inhibition , and the conditioned fear phenotypes studied in this article (Parker et al 2012b). This study makes several key contributions over previous work in this area.…”
mentioning
confidence: 99%
“…AILs have been employed in several previous studies to successfully map QTL for complex traits in mice, including locomotor activity , muscle weight (Lionikas et al 2010), red blood cell characteristics (Bartnikas et al 2012), body weight , methamphetamine sensitivity (Parker et al 2012a), prepulse inhibition , and the conditioned fear phenotypes studied in this article (Parker et al 2012b). This study makes several key contributions over previous work in this area.…”
mentioning
confidence: 99%
“…For example, in a nine-generation advanced intercross used for fine mapping body weight in chickens, BESNIER et al (2011) could only detect five of the nine QTL that were earlier found with the original F2 population. Similar results have been found in advanced crosses of maize (HUANG et al 2010) and mice (WANG et al 2003;LIONIKAS et al 2010).…”
Section: Finer Scale Qtl Localisation and Annotation Of The Qtl-contasupporting
confidence: 87%
“…Although the use of advanced intercross populations for mapping the genetic basis of traits improves accuracy by reducing confidence intervals around QTLs (HUANG et al 2010;LIONIKAS et al 2010), the accumulation of recombination events and subsequent break down of linkage disequilibrium among loci in later generations of an advanced intercross (DARVASI and SOLLER 1995), may lead to significant deviation of QTL effect positions from those observed in earlier (e.g. F2) generations (BESNIER et al 2011).…”
Section: Finer Scale Qtl Localisation and Annotation Of The Qtl-contamentioning
confidence: 99%
See 2 more Smart Citations